In Vivo Study of the Therapeutic Activity of ASKOLIT, Anti-Ulcer, and ASXAQ Plant Food Supplement Extracts Against Gastric Ulcers and Colitis in Rodent Models - Ibragim R. Askarov; Khabibullo N. Kodirov (Peerian Journals Publishing, 2025)
This study investigates the therapeutic efficacy of three novel plant-based food supplements— ASKOLIT, Anti-Ulcer, and ASXAQ—against experimentally induced gastric ulcers and colitis in ro0dent models. Using standardized animal protocols, we assessed histopathological, biochemical, and macroscopic outcomes to evaluate healing, antiinflammatory, and mucosal protective effects. These supplements, derived from synergistic blends of medicinal herbs with known gastroprotective properties, demonstrated significant protective and curative potential, suggesting a promising role in managing gastrointestinal disorders.
Keywords: ulcerative colitis; peptic ulcer disease askolit; asxaq